MALDI Spectra Database for Rapid Discrimination and Subtyping of Mycobacterium kansasii - Murugaiyan, Jayaseelan; Lewin, Astrid; Kamal, Elisabeth; Bakuła, Zofia; van Ingen, Jakko; Ulmann, Vit; Unzaga Barañano, Miren J.; Humięcka, Joanna; Safianowska, Aleksandra; Roesler, Uwe H.; Jagielski, Tomasz (Frontiers in Microbiology, 2018)
Mycobacterium kansasii is an emerging non-tuberculous mycobacterial (NTM) pathogen capable of causing severe lung disease. Of the seven currently recognized M. kansasii genotypes (I-VII), genotypes I and II are most prevalent and have been associated with human disease, whereas the other five (III-VII) genotypes are predominantly of environmental origin and are believed to be non-pathogenic. Subtyping of M. kansasii serves as a valuable tool to guide clinicians in pursuing diagnosis and to initiate the proper timely treatment. Most of the previous rapid diagnostic tests for mycobacteria employing the matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF MS) technology focused on species-level identification. The purpose of this study was to establish MALDI-TOF MS reference spectra database for discrimination of M. kansasii at the genotype level. A panel of 32 strains, representatives of M. kansasii genotypes I-VI were selected, whole cell proteins extracted and measured with MALDI-TOF MS. A unique main spectra (MSP) library was created using MALDI Biotyper Compass Explorer software. The spectra reproducibility was assessed by computing composite correlation index and MSPs cross-matching. One hundred clinical M. kansasii isolates used for testing of the database resulted in 90 % identification at genus-level, 7 % identification at species-level and 2% identification was below the threshold of log score value 1.7, of which all were correct at genotype level. On the other hand, one strain was not identified, while 37% of strains were identified at species level, 40% at genus level and 23% was not identified with the manufacturer’s database. The MALDI-TOF MS was proven a rapid and robust tool to detect and differentiate between M. kansasii genotypes. It is concluded that MALDI-TOF MS has a potential to be incorporated into the routine diagnostic workflow of M. kansasii and possibly other NTM species.